Use of a Gastric Juice-Based PCR Assay To Detect Helicobacter pylori Infection in Culture-Negative Patients - Yoshida, Haruhiko (American Society for Microbiology, 1998)
A gastric juice-based PCR assay was compared with culture, microscopy, and a rapid urease test with specimens from 114 subjects. The PCR and conventional tests were positive for 76 and 62% of the subjects, respectively. The prevalence of gastroduodenal disease and seropositivity for anti-Helicobacter pylori immunoglobulin G were similarly high among conventional-test-positive and PCR-only-positive subjects compared to all-negative ones. The PCR assay is recommended to confirm the H. pylori status of culture-negative peptic-ulcer patients.